The Ethical Impacts by the United Nations Security Council (UNSC) Peacekeeping Missions in Mitigating Complex African Conflicts: A Qualitative Approach - Zibusiso, Nyoni; Mahuku, Darlington N. (Indonesian Journal of Community Services, 2025)
The United Nations Security Council (UNSC), one of the main UN bodies, is charged with promoting and upholding international peace and security. The UNSC is empowered by resolutions to deploy peacekeeping forces to any crisis zone to preserve international peace and security. However, these UN peacekeeping missions have encountered moral conundrums in the course of their work using the DRC as a case study, this research sought to investigate the ethical dilemmas faced by UNSC peacekeeping operations in complex African complexes. The main objective of the study was to critically examine the ethical and community dilemmas that the UNSC's peacekeeping missions in the DRC had to deal with. The study used the constitutive theory as the main theory that formed the hinge of the study. Qualitative data was gathered from the Military, Police, Civilian, Prisons and Correctional Services, and diplomats who were selected for their particular experience and proficiency in peacekeeping missions. NVIVO 11 was used to analyze the collected data, and the results yielded themes that the researcher then presented verbatim. In this regard, the study revealed that the UNSC peacekeeping force is confronted with several moral dilemmas, including social disintegration, human casualties, constitutional crises, and UN Charter violations that have resulted in ceaseless wars. Therefore, the study recommends that African nations make security-related investments if they want to protect their national sovereignty from outside influence, reliance, and meddling. African nations must also be self-sufficient and not overly reliant on other nations to solve their problems.